An adaptive algorithm for performance enhancement of long-haul MMW/RoF system for next generation mobile communications. (7th July 2022) - Tuan, Nguyen Van; Dien, Nguyen Van; Nhat, Nguyen Dong; Son, Tran The; Dao, Duy-Tuan; Toan, Nguyen Khanh; Hung, Nguyen Tan
Radio over fibre (RoF) and millimetre wave (MMW) are regarded as the most promising solutions to provide high-capacity, long-distance data transport between base stations and core network in the future heterogeneous radio access networks that support both cloud and edge computing paradigms. In this paper, we propose an adaptive algorithm to optimise and determine a set of important link parameters for a MMW/RoF integrated system based on 10 Gb/s QPSK modulation format and heterodyne coherent detection. We develop analytical models of main components and derive a closed-form expression of system performance such as Q, SNR and BER . The adaptive algorithm is successfully applied to determine important link parameters including laser power, local oscillator power, optical amplifier location and gains so that the overall performance could be enhanced at an acceptable level corresponding to the varied propagation length from 200 km to 300 km. BERs of well below the 10 -9 .